A Longitudinal Exploration of the Effect of Official Processing and Sanctioning on the Academic and Criminal Careers of College Students - Khey, Dave N. (American journal of criminal justice, 2010)
This study examines the effect of official processing and sanctioning on the academic and criminal careers of a sample of college students from a large university in a southeastern college town. Using a series of OLS and logistic regression models, the results indicated that offense frequency and severity are risk factors for dropping out/or being dismissed from college, whereas membership in a sorority or fraternity is a protective factor. Additional analyses demonstrated that the severity of punishment as well as the type of punishment (e.g., judicial affairs punishment, criminal justice system punishment) also had a significant effect on future offending. Study limitations and policy implications are also discussed.